PENGEMBANGAN GAME EDUKASI â€œLINGED MATHâ€ PADA MATERI LINGKARAN SMP - Nurbuono, Mousthapaa; Kristiana, Arika Indah; Hussen, Saddam; Wihardjo, Edy; Murtikusuma, Randi Pratama (EDUPEDIA, 2024)
Educational games are games specifically designed with educational themes to get learning outcomes. This research develops an educational game "Linged Math" which is designed to make it easier for students to understand circle material, cirle material is one of the materials at the junior high school level which is difficult for students to understand. The purpose of this research is to develop educational game products based on pcgames use Construct 3 software to increase students' understanding of valid, practical, and effective circle material. This research model uses a 4-D development model, namely define, design, develop, and disseminate. This educational game was tested on class VIII students of SMPN 7 Jember. Data collection methods in this study used observation, tests, and user response questionnaires. The results of this study indicate that the level of validation of the educational game "Linged Math" from the validator is 3.84 so that it is categorized valid. The percentage of the practicality level of the educational game "Linged Math" from the results of the user response questionnaire was 86.25% which was categorized as very good. The level of effectiveness is obtained from the average N-Gain of the overall results of the student's pre-test and post-test of 0.77 so that it is categorized as high or effective. Based on the results of these data, the educational game "Linged Math" is said to be valid, practical, and effective.